Aquabis(5-methylpyrazine-2-carboxylato)zinc(II) trihydrate - Cui, Yong-Ming (International Union of Crystallography, 2009)
In the title compound, [Zn(C(6)H(5)N(2)O(2))(2)(H(2)O)]·3H(2)O, the Zn(II) centre is five-coordinated by two O,N-bidentate Schiff base ligands and one O atom from a water molecule in a slightly distorted square-pyramidal geometry. In the crystal, the complex and uncoordinated water molecules are linked by O—H⋯O, O—H⋯N and C—H⋯O hydrogen bonds, forming a three-dimensional network.